THE IMPACT OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT CV MAJU KARSA BERSAMA - Yulies Herni; Dira Karlina; Sri Purni Hernawati (International Journal Multidisciplinary Science, 2025)
This study examines the impact of work environment and work motivation on employee performance at CV. Maju Karsa Bersama. Using a quantitative research approach, data were collected through surveys and analyzed using statistical methods. The results indicate that a conducive work environment, including adequate lighting, ventilation, and minimal noise, significantly enhances employee productivity. Employees who work in a well-managed environment tend to be more efficient and engaged in their tasks. Additionally, work motivation plays a crucial role in improving performance. Companies that provide financial and non-financial incentives, such as bonuses, career development programs, and employee recognition, can enhance motivation and commitment. The study also finds that the combination of work environment and motivation has a stronger influence on performance than either factor alone. These findings highlight the importance of strategic workforce management in optimizing employee productivity and job satisfaction, ultimately contributing to organizational success.